Pendidikan Akhlak Islami sebagai Strategi Preventif Cyberbullying pada Remaja Muslim - Afroo, Fakhriyah Annisa; Nurjanah, Nurjanah; Yudita, Anisa (An-Nuha, 2025)
The rapid development of digital technology provides significant opportunities for Muslim adolescents but also poses serious challenges, particularly the growing phenomenon of cyberbullying. This issue negatively affects adolescents’ psychological, social, and academic conditions, thereby requiring preventive strategies that are not only technical but also grounded in moral and spiritual education. This study aims to analyze Islamic moral education (akhlak Islami) as a preventive strategy against cyberbullying among Muslim adolescents. The research employed a qualitative method with a library research approach and descriptive-analytical analysis of primary and secondary literature related to Islamic education, Islamic ethics, and the phenomenon of cyberbullying. The findings reveal that ten core values of Islamic morality qaulan karīma (kind speech), ḥusnuzan (positive thinking), tawāḍuʿ (humility), ṣabr (self-control), amar maʿrūf nahi munkar (enjoining good and forbidding evil), ṣidq (honesty), amānah (responsibility), iḥsān (sincere benevolence), ukhuwwah islāmiyyah (brotherhood), and ʿadālah (justice) function as a moral filter in digital interactions. Internalizing these values enables adolescents to avoid deviant behaviors while strengthening their psychological resilience in online environments. The study emphasizes the importance of synergy between schools, families, and communities in preventing cyberbullying. Theoretically, this research contributes to the development of contemporary Islamic education responsive to digital challenges, while practically offering implications for schools, parents, and policymakers in fostering a healthy, ethical, and Islamically grounded digital ecosystem